Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) terhadap Hasil Belajar Matematika Siswa - Abidin, Zainal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The purpose of this study was to determine the effect of the Student Teams Achievement Division (STAD) cooperative learning model on the mathematics learning outcomes of students class VII MTs. NW Senyiur. While the type of research used in this study is quasi-experimental. The sampling technique uses saturated sampling. The research instrument was in the form of a learning achievement test sheet. From the results of data analysis on student test results, there was an average score in the experimental class of 81.33 with the highest score of 100 and the lowest score of 65, while the average score in the control class was 60.17 with the highest score of 80 and the lowest score of 40. Then based on the results of the t-test obtained tcount of 8.29 and ttable of 2.00, because tcount ≥ ttable then Ha is accepted and H0 is rejected. So we can conclude that there is an influence of the Student Teams Achievement Division (STAD) cooperative learning model on the mathematics learning outcomes of students class VII MTs. NW Senyiur.